'Disaster citizenship': an emerging framework for understanding the depth of digital citizenship in Pakistan. Issue 2 (3rd April 2018) - Siddiqi, Ayesha
Abstract : In recent years, the Pakistani state has made significant advances in formalising and universalising citizenship through the digitisation of citizenship numbers. The National Database and Registration Authority (NADRA) is at the forefront of this initiative, which has now covered 96% of Pakistan's 180 million citizens. The state successfully used this digitisation of citizenship to reach out to its citizens in the aftermath of a large-scale flooding disaster in 2010 and 2011. The universal cash transfer programme instituted for disaster-affected households used citizenship numbers to identify and then provide ATM cards to those domiciled in the worst-affected regions. This paper draws upon my fieldwork done in 2012–2013 in Lower Sindh and argues that while still in its infancy, a new form of 'disaster citizenship' is visible in southern Pakistan, which is driven partially by this digitisation of citizenship in the country. It explores the post-disaster political space where state actors and citizens came to interact with each other, and argues that these informal and unplanned interactions overlapped with formal policy to result in a new and emerging form of 'disaster citizenship' in the region.